Women’s struggle and media reform: The Swedish Women’s Associations’ Radio Committee, 1933–1940 - Stiernstedt Fredrik (Nordic Journal of Media Studies)
This article contributes to a social history of Swedish broadcasting through an analysis of a movement for media reform: the Swedish Women’s Associations’ Radio Committee, formed in 1933 and operating until 1940. The committee was a joint effort by many established women’s organisations in Sweden, formed with the goal of strengthening the role of women in the developing public service radio, and especially providing a platform for women to raise demands on influence in the decision-making around the development of this new media form. In this article, I analyse the Swedish Women’s Associations’ Radio Committee and their work in the 1930s and ask what they did, how they did it, and with what effects? In what ways can their work be understood as a movement for media reform? The analysis builds on archival material documenting the Swedish Women’s Associations’ Radio Committee, as well as secondary sources such as memoirs and newspaper materials.